2016
DOI: 10.1590/1413-785220162403142182
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Abdominal Desmoid Tumor: Local Recurrence and Treatment Options

Abstract: Objective: To evaluate the rate of local recurrence of extra-abdominal desmoid tumor and compare the outcomes of surgical treatment and conservative treatment.Methods: Twenty one patients (14 women and seven men), mean age 33.0±8.7 years old, with a diagnosis of desmoid tumor were evaluated. The mean follow-up period was 58.5±29.0 months. Fourteen cases involved the lower limbs, four cases involved the upper limbs, and three cases involved the trunk. The average tumor size was 12.7±7.5 cm. Of the 21 patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…A study of 21 patients with DT has shown that gender, age, localization and number of previous recurrences does not affect the recurrence rate of the tumor [11]. We presented a challenging case of DT in which we supported the notion of surgery as treatment of choice, but with functional preservation of anatomical structures.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…A study of 21 patients with DT has shown that gender, age, localization and number of previous recurrences does not affect the recurrence rate of the tumor [11]. We presented a challenging case of DT in which we supported the notion of surgery as treatment of choice, but with functional preservation of anatomical structures.…”
Section: Discussionsupporting
confidence: 61%
“…Patients with DT usually are young females between 15-35 years [11]. Our patient was 36 year old male, and he was younger, compared to patients described in publications with similar localization (lower limbs) of this tumor type [9,10,12,17,18].…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations